2020
DOI: 10.1038/s41598-020-60681-4
|View full text |Cite
|
Sign up to set email alerts
|

Sialylated N-glycan profile during acute and chronic infections with Toxoplasma gondii in mice

Abstract: Toxoplasma gondii is associated with physiological and psychiatric perturbations. The immune response is interrelated to the progress of anhedonia and despair symptoms of T. gondii-infected subjects. We recently reported that serum N-glycans were altered in mice displayed depressive-like behaviors. However, a novel biomarker that correlated to T. gondii infection and associated behaviors is demanded. Glycomics has been used to find affected glycoproteins during depression. The objective of this study is to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…However, in a study conducted by Mahmoud et al, depression was correlated to reactivated T. gondii and not chronic infection of T. gondii in BALB/c mice [ 106 ]. In a study conducted in 2020, a similar result was found where chronic infection of T. gondii did not appear to have correlation with depression, yet there was a correlation with the acute stage [ 107 ]. Multiple other studies found no association between latent T .…”
Section: Methodology and Resultsmentioning
confidence: 62%
“…However, in a study conducted by Mahmoud et al, depression was correlated to reactivated T. gondii and not chronic infection of T. gondii in BALB/c mice [ 106 ]. In a study conducted in 2020, a similar result was found where chronic infection of T. gondii did not appear to have correlation with depression, yet there was a correlation with the acute stage [ 107 ]. Multiple other studies found no association between latent T .…”
Section: Methodology and Resultsmentioning
confidence: 62%
“…Rhesus macaques, in particular have shown high similarities with humans in terms of lymphatic pathology and immune responses 38 , 39 . However, application of serum or IgG glycoprofiling for infectious diseases has focused mostly on infection with viral or bacterial pathogens 22 , 47 with very few studies addressing infections with eukaryotic parasites such as protozoa 48 50 or metazoan flatworms and nematodes 48 , 51 , 52 .…”
Section: Introductionmentioning
confidence: 99%
“…These glycans have been shown to modulate interactions between cells, between cells and their tissue micro-environment, as well as to mediate immune cell and growth factor signaling ( Ohtsubo and Marth, 2006 ; Moremen et al, 2012 ). Pronounced changes in the structure of the glycans attached to lipids and proteins have been reported in tissue development and disease progression in humans as well as model organisms such as zebrafish, fruit flies, and mice ( Wang et al, 2001 ; Nakakita et al, 2005 ; Ten Hagen et al, 2009 ; Baas et al, 2011 ; Chu et al, 2013 ; Hanzawa et al, 2017 ; Frappaolo et al, 2018 ; Cervoni et al, 2020 ; Rehan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%